A practical guidance for assessments of sedentary behavior at work: A PEROSH initiative. (September 2017) - Holtermann, Andreas; Schellewald, Vera; Mathiassen, Svend Erik; Gupta, Nidhi; Pinder, Andrew; Punakallio, Anne; Veiersted, Kaj Bo; Weber, Britta; Takala, Esa-Pekka; Draicchio, Francesco; Enquist, Henrik; Desbrosses, Kevin; et al.
Abstract: Sedentary behavior is defined as sitting or lying with low energy expenditure. Humans in industrialized societies spend an increasing amount of time in sedentary behaviors every day. This has been associated with detrimental health outcomes. Despite a growing interest in the health effects of sedentary behavior at work, associations remain unclear, plausibly due to poor and diverse methods for assessing sedentary behavior. Thus, good practice guidance for researchers and practitioners on how to assess occupational sedentary behavior are needed. The aim of this paper is to provide a practical guidance for practitioners and researchers on how to assess occupational sedentary behavior. Ambulatory systems for use in field applications (wearables) are a promising approach for sedentary behavior assessment. Many different small-size consumer wearables, with long battery life and high data storage capacity are commercially available today. However, no stand-alone commercial system is able to assess sedentary behavior in accordance with its definition. The present paper offers decision support for practitioners and researchers in selecting wearables and data collection strategies for their purpose of study on sedentary behavior. Valid and reliable assessment of occupational sedentary behavior is currently not easy. Several aspects need to be considered in the decision process on how to assess sedentary behavior. There is a need for development of a cheap and easily useable wearable for assessment of occupational sedentary behavior by researchers and practitioners. Highlights: There is a growing occupational and public interest in sedentary behavior, defined as sitting or lying with low energy expenditure. Many small-size consumer wearables, with long battery life and high data storage capacity are commercially available. No current stand-alone commercial system is able to assess sedentary behavior in accordance with its definition. There is a need for a practical guidance for practitioners and researchers to appropriately assess sedentary behaviour based on purpose of study. The proposed practical guidance presents an overview of characteristics of wearables and factors to consider for sedentary behavior assessment.